High engagement, high quality: A guiding framework for developing empirically informed asynchronous e‐learning programs for health professional educators. (16th January 2017) - Sinclair, Peter M.; Levett‐Jones, Tracey; Morris, Amanda; Carter, Ben; Bennett, Paul N.; Kable, Ashley
Abstract : E‐learning involves the transfer of skills and knowledge via technology so that learners can access meaningful and authentic educational materials. While learner engagement is important, in the context of healthcare education, pedagogy must not be sacrificed for edu‐tainment style instructional design. Consequently, health professional educators need to be competent in the use of current web‐based educational technologies so that learners are able to access relevant and engaging e‐learning materials without restriction. The increasing popularity of asynchronous e‐learning programs developed for use outside of formal education institutions has made this need more relevant. In these contexts, educators must balance design and functionality to deliver relevant, cost‐effective, sustainable, and accessible programs that overcome scheduling and geographic barriers for learners. This paper presents 10 guiding design principles and their application in the development of an e‐learning program for general practice nurses focused on behavior change. Consideration of these principles will assist educators to develop high quality, pedagogically sound, engaging, and interactive e‐learning resources.